A Study of the Efficiency of the Two-Phase Anaerobic Degradation System 2PAD in The Different Temperature Ranges - Hadid, Mahmoud; Aladeeb, Ziad (Latakia University Journal -Engineering Sciences Series, 2019)
The Average thermal range (Mesophilic) [25 – 40]oC is the optimal range for the process of anaerobic treatment and specifically the temperature [34 -37]oC where the microorganisms that lead the anaerobic treatment process are at their highest activity which gives high efficiency to the treatment process and biogas production process, also the Two-Phase Anaerobic Degradation System 2PAD is used to increase the efficiency of anaerobic treatment process compared to the Conventional Single-Phase Anaerobic Digestion System AD. This research presents a study of the efficiency of the Two-Phase Anaerobic Degradation System 2PAD in the different ranges of temperature through the treatment of three samples of wastewater from slaughterhouses, where the efficiency of COD removal was 81.65% and the efficiency of BOD removal was 88.00% and the efficiency of TSS removal was 39.68% while biogas production reached 0.24 liter from each liter of the sample at 40o C and during a 10-day hydraulic retention time HRT for the first sample A (CODin= 3760 mg/l, BODin=2500 mg/l, TSSin=368 mg/l), and the efficiency of COD removal was 64.74% and the efficiency of BOD removal was 71.43% and the efficiency of TSS removal was 56.09% while biogas production reached 0.16 liter from each liter of the sample at 20o C and during a 24-day hydraulic retention time HRT for the second samples B (CODin=1730 mg/l, BODin=1400 mg/l, TSSin=312 mg/l). and the efficiency of COD removal was 83.38% and the efficiency of BOD removal was 89.29% and the efficiency of TSS removal was 42.11% while biogas production reached 0.28 liter from each liter of the sample at 34o C and during a 17-day hydraulic retention time HRT for the third sample C (CODin=3850 mg/l, BODin=2800 mg/l, TSSin=475 mg/l). يعتبر المجال الحراري المتوسط (Mesophilic) [25-40]oC المجال الأمثل لسير عملية المعالجة البيولوجية اللاهوائية وتحديداً درجة الحرارة [34-37]oC حيث تكون الأحياء الدقيقة التي تقود عملية المعالجة اللاهوائية في أعلى نشاط لها الأمر الذي يعطي كفاءة عالية لعملية المعالجة وعملية إنتاج الغاز الحيوي، أيضاً يستخدم نظام المعالجة اللاهوائية ثنائي الطور (Two-Phase Anaerobic Degradation System) 2PAD لرفع كفاءة عملية المعالجة اللاهوائية بالمقارنة مع نظام المعالجة اللاهوائية التقليدي (Conventional Single-Phase Anaerobic Digestion System) AD. يعرض هذا البحث دراسة كفاءة نظام المعالجة اللاهوائية ثنائي الطور 2PAD في المجالات المختلفة من درجة الحرارة وذلك من خلال معالجة ثلاث عينات من مياه الصرف الناتجة عن المسالخ، حيث كانت كفاءة إزالة COD 81.65 %وكفاءة إزالة BOD 88.00% وكفاءة إزالة TSS 39.68% بينما بلغ إنتاج الغاز الحيوي 0.24 Liter من كل 1 Liter من العينة في درجة الحرارة 40oC وخلال زمن بقاء هيدروليكي HRT 10 day بالنسبة للعينة الأولى A (CODin=3760 mg/l, BODin=2500 mg/l, TSSin=368 mg/l)، و كانت كفاءة إزالة COD 64.74% وكفاءة إزالة BOD 71.43% وكفاءة إزالة TSS 56.09% بينما بلغ إنتاج الغاز الحيوي 0.16 Liter من كل 1 Liter من العينة في درجة الحرارة 20oC وخلال زمن بقاء هيدروليكي HRT 24 day بالنسبة للعينة الثانية B (CODin=1730 mg/l, BODin=1400 mg/l, TSSin=312 mg/l)، وكانت كفاءة إزالة COD 83.38% وكفاءة إزالة BOD 89.29% وكفاءة إزالة TSS 42.11% بينما بلغ إنتاج الغاز الحيوي 0.28 Liter من كل 1 Liter من العينة في درجة الحرارة 34oC وخلال زمن بقاء هيدروليكي HRT 17 day بالنسبة للعينة الثالثة C (CODin=3850 mg/l, BODin=2800 mg/l, TSSin=475 mg/l).